The impact of government size on economic growth in Chinese prefecture-level cities: does fiscal transparency matter? - Liu, Cong; Abd Ghani, Judhiana; Thinng, Wency Bui Kher (Universiti Malaysia Sarawak, 2025)
Recent studies have examined how institutions influence the relationship between government size and economic growth. However, they have largely overlooked the significance of fiscal transparency, which can help bridge the information gap between governments and citizens. Furthermore, these studies typically concentrate on national or state levels, neglecting local governments that are primarily responsible for delivering public goods. This study investigates the impact of local government size on economic growth in Chinese prefecture-level cities, emphasizing the moderating role of fiscal transparency. We employ a dynamic panel model with two-way fixed effects and the Generalized Method of Moments (GMM) for estimation. The data encompasses 283 cities from 2013 to 2022. The main findings are as follows: In the absence of fiscal transparency, local government size positively influences economic growth; however, fiscal transparency negatively moderates this relationship. Moreover, as fiscal transparency increases, the positive effect diminishes and becomes statistically insignificant once it exceeds a certain threshold. Robustness checks using alternative measures and estimation techniques validate the results. The primary originality of this study lies in quantifying the moderating role of fiscal transparency in the relationship between government size and growth. These findings challenge the New Institutional Theory, which asserts that institutions directly drive growth, and provide a novel perspective on the interplay between government size and economic performance, offering valuable insights for policymakers aiming to balance government size and transparency for sustainable development.